Transformation of Indian Foreign Policy in the Narendra Modi Era - Duran, Hasan; Toprak, Yusra (Journal of Applied And Theoretical Social Sciences, 2022)
This study focuses on the aims of the Baharatiya Janata Party (BJP) government, which came to power under the leadership of Narendra Modi in 2014, regarding India's foreign policy, its policies that are different from the previous governments, and the results of these policies. The administration led by Narendra Modi aims to ensure that India is recognized as an important power in the region through breakthroughs such as the Move East, Neighborhood First policy; In order to realize the multipolar world order, it has determined as India's foreign policy priority to maintain win-win relations with the states that are forceful in the protection of India's international and regional interests within the framework of the concept of strategic autonomy and to emphasize soft power elements. In this study, the impact of the discourse and policies in which diplomacy is used as an effective tool, unlike previous governments, on India's close circle and the international system is evaluated.